RELATIONS BETWEEN THE DIFFERENCES OF DIFFERENT PROPERTIES OF FREONES ON THE SATURATION LINES UPON LIQUID-VAPOR PHASE TRANSITION - B. A. Arutyunov; E. V. Rytova; G. P. Kalymbet (Тонкие химические технологии)
To construct a generalized dependency, a scale for the unknown quantities and variables must be selected. The states of points are located in P-V-T (pressure-volume-temperature) space. The scale for the construction of generalized dependences of the studied properties and variables of the problem must be sustainable. In order to find a sustainable transition from liquid to vapor the behavior of the characteristic function of free energy is investigated. Since the phase transition occurs at a constant temperature, free energy is equal to expansion work. In the analysis of the liquid-vapor transition, the curve of the temperature dependence of expansion work for all investigated substances has a maximum. The temperature corresponding to the maximum expansion work is denoted by Tm. It was noted that temperature Tm associated with Tc (critical) with the simple relation Tm =0.76Tс with a spread of 2%. Naturally, this state corresponds to the free energy minimum value, and in accordance with the principle of minimality of characteristic functions of this process is stable. Therefore, the parameters of this process were chosen as the bringing scale in the construction of dimensionless dependencies. In this paper we use the method of constructing generalized dependencies in the reduced form, based on the characteristic functions minimality principle. Approximating formulas were obtained for calculating reduced heat of evaporation from reduced density, entropy, and freons surface tension. The reduction scale is considered on the liquid and vapor saturation line under substances consideration. The characteristic functions minimality principle is used. In the course of the analysis, calculation formulas were derived for pure freons both individually and in a combined form. The interrelation between the differences of these thermodynamic properties on the saturation line during a liquid-vapor phase transition is shown. This makes it possible to determine some properties using other methods by calculation.